2017
DOI: 10.1177/1745499917740657
|View full text |Cite
|
Sign up to set email alerts
|

Is ‘summer’ reading loss universal? Using ongoing literacy assessment in Malawi to estimate the loss from grade-transition breaks

Abstract: Summer learning loss – decreased academic performance following an extended school break, typically during the period after one grade ends and before another grade starts – is a well-documented phenomenon in North America, but poorly described in sub-Saharan African contexts. In this article, we use the term ‘grade-transition break’ loss in lieu of ‘summer’ loss to refer to the period after one grade ends and before another grade starts. This study analyses data from early grade reading assessments in Malawi, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…While smaller in scale, widespread school closures are not unique to COVID-19: teacher strikes, summer breaks, earthquakes, viruses such as influenza and Ebola, and weather-related events cause schools to close. Closures result in large learning losses, which have been documented in North America, Western Europe, and Sub-Saharan Africa (Cooper et al 1996;Slade et al 2017;Jaume and Willen 2019;Andrabi, Daniels, and Das 2020). To mitigate learning loss in the absence of school, high-income families have access to alternative sources of instruction-books, computers, internet, radio, television, and smart phones-that many low-income families do not (Bacher-Hicks et al 2020;Chetty et al 2020;Engzell et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…While smaller in scale, widespread school closures are not unique to COVID-19: teacher strikes, summer breaks, earthquakes, viruses such as influenza and Ebola, and weather-related events cause schools to close. Closures result in large learning losses, which have been documented in North America, Western Europe, and Sub-Saharan Africa (Cooper et al 1996;Slade et al 2017;Jaume and Willen 2019;Andrabi, Daniels, and Das 2020). To mitigate learning loss in the absence of school, high-income families have access to alternative sources of instruction-books, computers, internet, radio, television, and smart phones-that many low-income families do not (Bacher-Hicks et al 2020;Chetty et al 2020;Engzell et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…moving between grades or years). Learning loss over school holidays has been commonly reported (Slade et al 2017 ), and has been found to disproportionately affect children in low-income families (Quinn et al 2016 ). For example, children who are out of school for the summer holidays in Latin America lose nearly three months of prior learning (Busso and Munoz 2020 ).…”
Section: School Disruptions and Educational Outcomesmentioning
confidence: 99%
“…For example, children who are out of school for the summer holidays in Latin America lose nearly three months of prior learning (Busso and Munoz 2020 ). In Malawi, Timothy Slade and colleagues ( 2017 ) reported a 0.38 standard deviation decrease in reading scores during the three-month transition from Grade 1 to Grade 2. During a similar transition in Ghana, foundational numeracy test differences represented a 66% loss in learning gains, with a complete elimination of learning gains for those without books or reading materials at home (Sabates and Carter 2020 ).…”
Section: School Disruptions and Educational Outcomesmentioning
confidence: 99%
“…For this reason, most research has examined disruptions due to disasters or looked at school holidays or transitions. Learning loss over school holidays is commonly reported (Slade et al 2017) and disproportionately affects children in low income families (Quinn et al 2016). Children out of school for the summer holidays in Latin America loose nearly three months of prior learning (Busso and Munoz 2020).…”
Section: School Disruptions and Educational Outcomesmentioning
confidence: 99%